Representasi Perempuan Indonesia Dalam Ajang Penghargaan Televisi (Studi Feminisme pada Penghargaan Indihome Women Award Di Metro TV) - Ahmad Toni (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2014)
Television personality award for the motor marketing television programs itself, the need to raise the rating and share. The awards were recently held by MetroTV devoted to female finalists Indonesia called modern Kartini. This study aimed to describe the representation of women in the awards Indihome Women Award at Metro TV. The method used consciousness-raising method, a method to generate knowledge and awareness in terms of women's issues and women movement within the frame of the mass media (television). This study used a qualitative descriptive method with emphasis on the reality of the media that have a relationship or context with social reality in Indonesia. The results showed the awards event Indihome Women Award in Metro women disepresentasikan as duality and ambiguity in the system of nation building; (1) Women look no further indicate the identity and values alignment on national development map but are represented at the level of the worse off, (2) Women made a movement which is represented as a capitalist agent, (3) Women and the movement into the implementation of a number of representations of themselves and movements performed in the frame of self falsehood.